Advanced Nanoparticle Therapeutics for Targeting Neutrophils in Inflammatory Diseases - Byun, Min Ji; Nakasone, Elizabeth S.; Shin, Ha Eun; Lee, Hyojin; Park, Jong-Chan; Lee, Wonhwa; Park, Wooram; Park, Chun Gwon; Park, Juwon; Kim, Se-Na (Wiley-Blackwell, 2025)
Neutrophils, the most abundant leukocytes in human blood, play a critical role in the initial response to acute infection and injury. Activated neutrophils exert three primary effector functions: phagocytosis, degranulation of proteolytic enzymes into pericellular spaces, and generation of neutrophil extracellular traps (NETs). However, dysregulated neutrophil function can lead to tissue damage and inflammation, resulting in organ dysfunction that ultimately contributes to the progression of various diseases. Given the implication of neutrophils in the pathogenesis of diseases arising from chronic inflammation, exploring emerging therapies targeting these cells is critical for developing more effective treatment options. This review highlights nanotechnology-based therapeutic strategies aimed at modulating neutrophil activity and NET formation, with a focus on nanoparticles (NPs) and hydrogels. NPs-based delivery systems can regulate excessive neutrophil activity through targeted delivery of anti-inflammatory drugs, alteration of gene expression, induction of cell death, or inhibition of neutrophil recruitment. Additionally, various nanotechnology-based therapeutics can inhibit NET formation or degrade NETs following neutrophil activation. NPs can also be internalized by neutrophils and utilized as carriers, facilitating localized therapeutic delivery as neutrophils are recruited to inflammatory sites. The importance of targeting or harnessing neutrophils are explained and we discuss therapeutic strategies to control their activity, which may aid in designing future treatments for neutrophil-mediated inflammatory diseases.